Virulence - associated genes in Avian Pathogenic Escherichia coli of turkey - Antonio Camarda; Davide Giovanardi; Raffaella Ceruti; Silvia Tagliabue; Donato Pennelli; Elena Circella (Italian Journal of Animal Science, 2010)
50 Escherichia coli (APEC-Avian Pathogenic Escherichia coli) strains and 15 E. coli (AFEC-Avian Faecal Escherichia coli) from turkeys affected by colibacillosis and from healthy turkeys were tested for the presence of eight different virulence-associated genes. Besides, APEC were serotyped. O78 has been the most detected serotyped. The presence of the tested virulence genes was prevalently related to the APEC isolates. With reference to serogroup, all the tested O78 resulted iss and irp2 positive. Besides, tsh e cva/cvi were respectively present in 88.9 and 83.3% of O78. Nevertheless, the finding of a not typeable strains equipped with all the eight tested virulence genes among the APEC isolates suggest the importance of a careful and complete characterisation of the isolate to evaluate the real potential pathogenic attitude of the bacterium.